THE HEREDITARY AND ENVIRONMENTAL VARIANCE OF GRAIN QUALITY OF WINTER SOFT WHEAT IN THE BELGOROD REGION - V. P. Netsvetaev; T. A. Ryzhkova; L. S. Bondarenko; I. P. Motorina; A. V. Petrenko; O. E. Nerubenko (Зерновое хозяйство России, 2018)
The article deals with the assessment results of the quality and productivity of winter soft wheat grain during the period of 2013-2015. The aggregation ability of endosperm protein due to the disulfide bonds (-S-S-) in flour ranged from 37+1.31 (2013) to 55.28+1.3 (2014) and 73.50+1.06 (2015). Respectively, the value of dough kneading was 3.53+0.13; 4.66+0.12 and 4.70+0.15 points (the device ‘Mikrolab’), which indicated about more favorable environmental conditions for the formation of the trait in 2014 and2015, in comparison with 2013. It has been determined that the largest differentiation among the samples according to the aggregation ability of protein complex and correlation of the trait with the value of dough kneading was noticed in2013. In the years contributing to higher levels of the peptides aggregation, the impact of the environment, which eliminates the hereditary differences in quality, significantly increases. The carriers of rye chromosome translocations 1RS.1BL and 1RS.1AL, in comparison with the typical wheat, possessed less aggregation of proteins, but in the years of 2013 and 2014 they significantly stood out in the productivity in the conditions of theBelgorod region.